A System for Tender Price Evaluation of Construction Project Based on Big Data. (2015) - Zhang, Yongcheng; Luo, Hanbin; He, Yi
Abstract: Tender price evaluation of construction project is one of the most important works for the clients to control project cost in the bidding stage. However, the previously underutilization of project cost data made the tender price evaluation of new projects lack of effective evaluation criterion, which brings challenge to cost control. With the improvement of companies' information technology application and the advent of big data era, the project cost-related data can be completely and systematically recorded in real time, as well as fully utilized to support decision-making for construction project cost management. In this paper, a system for tender price evaluation of construction project based on big data is presented, aiming to use related technique of big data to analysis project cost data to give a reasonable cost range, which contributes to obtaining the evaluation criterion to support the tender price controls. The paper introduced the data sources, data extraction, data storage and data analysis of the system respectively. A case study is conducted in a metro station project to evaluate the system. The results show that the system based on big data is significant for tender price evaluation in construction project.